2019
DOI: 10.1017/jfm.2019.348
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-layer stability of supercritical fluids in the vicinity of the Widom line

Abstract: We investigate the hydrodynamic stability of compressible boundary layers over adiabatic walls with fluids at supercritical pressure in the proximity of the Widom line (also known as the pseudo-critical line). Depending on the free-stream temperature and the Eckert number that determines the viscous heating, the boundary-layer temperature profile can be either sub-, trans-or supercritical with respect to the pseudo-critical temperature, T pc . When transitioning from sub-to supercritical temperatures, a seemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
2
38
1
Order By: Relevance
“…Lees & Lin (1946) demonstrated that it gives a necessary condition for a compressible boundary-layer flow to be inviscidly unstable. Ren et al (2019b) showed that a similar criterion is applicable for non-ideal gases. The distributions of d(ρ du/dy)/dy with y/δ are plotted in figure 4.…”
Section: Base Flow Solutionsmentioning
confidence: 97%
“…Lees & Lin (1946) demonstrated that it gives a necessary condition for a compressible boundary-layer flow to be inviscidly unstable. Ren et al (2019b) showed that a similar criterion is applicable for non-ideal gases. The distributions of d(ρ du/dy)/dy with y/δ are plotted in figure 4.…”
Section: Base Flow Solutionsmentioning
confidence: 97%
“…), that occur when the fluid evolves close to the critical point. Non-ideal fluids represent a research field of great importance for a wide range of applications; the work of Ren et al (2019b) aims to fill this gap.…”
Section: Overviewmentioning
confidence: 99%
“…The authors, however, point out that the Eckert number is better adapted than the Mach number to quantify the heat transfer dissipation due to friction and to the non-ideal gas effects. Ren et al (2019b) showed that the non-ideal behaviour of the gas stabilizes the boundary layer in the subcritical and supercritical regimes -i.e. when the temperature profile is fully below or above the pseudo-critical temperature T pc = 307.7 K, respectively.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations